The interaction of titanium films with water vapour over a wide range of pressures and exposures - Kandasamy, K.; Surplice, N.A. (Elsevier B.V., 1982)
The changes of work function phi and resistance R were studied when titanium films were exposed to water vapour at pressures p from UHV to 1.5 Torr and exposures q from 0-104 Torr s. The work function was reduced by 0.8+or-0.2 eV at p approximately 10-3 Torr and q approximately 1 Torr s, then at p approximately 10-2 Torr and q approximately 10-100 Torr s it began to increase again. Finally when p was increased to 1.5 Torr and q to approximately 104 Torr s phi was 0.1 eV less than the original value of phi for the clean film. The resistance was increased monotonically by about 10%. Hydrogen was evolved as each dose of water vapour was added to the film, and some of it was re-absorbed by the film. Complementary studies were made of the effects of mixtures H2 and O2, and of the successive sorptions H2O/O2/Ti and O2/H2O/Ti. The data implied that the decrease in phi was mainly due to the effects of the adspecies OH and H2O and the subsequent increase in phi may have been due to a mixed layer of oxides and hydroxide forming on the metal surface.